2022
DOI: 10.3390/cancers14174303
|View full text |Cite
|
Sign up to set email alerts
|

KRAS Pathway Alterations in Malignant Pleural Mesothelioma: An Underestimated Player

Abstract: Malignant pleural mesothelioma (MPM) is a rare, incurable cancer of the mesothelial cells lining the lungs and the chest wall that is mainly caused by asbestos inhalation. The molecular mechanisms of mesothelial carcinogenesis are still unclear despite comprehensive studies of the mutational landscape of MPM, and the most frequently mutated genes BAP1, NF2, CDKN2A, TP53, and TSC1 cannot cause MPM in mice in a standalone fashion. Although KRAS pathway alterations were sporadically detected in older studies empl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
4
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 46 publications
(102 reference statements)
2
4
0
Order By: Relevance
“…In support of our findings, asbestos has been reported to activate MAPK signaling and MPM cells have high MAPK activity [16,17]. Recent studies reveal that recurrent mutations in RTKs and KRAS are more common in MPM patients than previously reported [18][19][20]. Moreover, Merlin (encoded by NF2), a RAS antagonist, is inactivated in a substantial subset of MPM [6,7], which activates RAS/MAPK signaling.…”
Section: Discussionsupporting
confidence: 84%
See 1 more Smart Citation
“…In support of our findings, asbestos has been reported to activate MAPK signaling and MPM cells have high MAPK activity [16,17]. Recent studies reveal that recurrent mutations in RTKs and KRAS are more common in MPM patients than previously reported [18][19][20]. Moreover, Merlin (encoded by NF2), a RAS antagonist, is inactivated in a substantial subset of MPM [6,7], which activates RAS/MAPK signaling.…”
Section: Discussionsupporting
confidence: 84%
“…Although activating mutations along the MAPK pathway are absent or rare [6,7], it is noteworthy that the pathogenic potential of asbestos, an indisputable precipitant of mesothelioma [13][14][15], is associated with stimulation of MAPK signaling [16] and that MPM cell lines exhibit activation of the RAS/MAPK pathway [17]. Recent studies examining large cohorts or using alternative approaches show that sporadic and recurrent gain-of-function mutations in RTKs (e.g., EGFR) and RAS (e.g., KRAS) affect a significant proportion of MPM patients [17][18][19][20][21]. Collectively, these observations suggest that the RAS/MAPK pathway may play a role in MPM that has not been adequately investigated.…”
Section: Introductionmentioning
confidence: 99%
“…Despite these limitations, our findings are in line with previous studies [ 45 , 46 , 47 ], pointing to an underestimated importance of the RAS pathway in pleura malignant mesothelioma, as suggested by a significantly worse prognosis for patients carrying KRAS mutations. This study adds some new findings in the molecular profile and prognosis of MPM patients, which remain to be fully validated in broader studies and in the different MPM histotypes.…”
Section: Discussionsupporting
confidence: 90%
“…We have also shown two EGFR mutations not yet described in MM, which are considered functionally pathogenetic, in both exon 18 (p.P694T) and exon 19 (p.S752C). Previously, the authors of [ 45 ] reported a pathogenetic EGFR mutation in exon 19 (p.E746_A750del), suggesting the potential role of EGFR tyrosine kinase inhibitors (EGFR TKIs) as target therapy in selected cases of MPM.…”
Section: Discussionmentioning
confidence: 99%
“…Two of these regions are most frequently altered, namely, the CDKN2A–ARF gene at 9p21 and NF2 at 22q12, which behave as tumor suppressors [ 33 ]. Oncogene activation events encompass missense somatic mutation in KRAS and TP53, which have been detected in human MPM samples and are known to induce not only epithelial transformation but also aggressive mesotheliomas in animal models [ 34 ]. Transformation of human epithelial mesothelium is known to be regulated by ERKs transducers, which have different roles in the regulation of cell injury and repair, and a critical role is played by ERK2 [ 35 ].…”
Section: Genetic Alterations and Disease Stagementioning
confidence: 99%